2000
DOI: 10.1097/00005768-200006000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular volumes and hemodynamic responses to postexercise ischemia in healthy humans

Abstract: Activation of muscle metaboreceptors during OCCL increased MAP by elevating TPR. Despite the higher afterload and increased ESV, CO and SV were kept similar to resting values because EDV also increased, implying the involvement of the Frank-Starling mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 9 publications
8
43
2
1
Order By: Relevance
“…Therefore, it is possible that the experimental model of Farquhar and colleagues is one that is driven by peripheral vasoconstriction and not CO. Indeed, previous studies both support (8, 16 -18, 44, 48, 55, 60) and refute (6,18,44) any role for CO in mediating the pressor response during PEMI. As such, we would not expect the pressor response to fall during PEMI in HTN as in our model.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, it is possible that the experimental model of Farquhar and colleagues is one that is driven by peripheral vasoconstriction and not CO. Indeed, previous studies both support (8, 16 -18, 44, 48, 55, 60) and refute (6,18,44) any role for CO in mediating the pressor response during PEMI. As such, we would not expect the pressor response to fall during PEMI in HTN as in our model.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, other investigators have concluded that elevated arterial pressure stems from peripheral vasoconstriction, not CO (6,18,44). Several factors could account for these disparate conclusions, including differences in species, age, type, and intensity of exercise performed and experimental methodology.…”
Section: Perspectives and Significancementioning
confidence: 93%
“…From recent and early findings, it appears that the capacity to centralize blood volume and to increase venous return plays a pivotal role during the metaboreflex, and altered hemodynamic responses have been described where this capacity is impaired (4,13,33,53). In the present investigation, VFR was used to investigate venous return.…”
Section: Discussionmentioning
confidence: 93%
“…Recent physiological studies, with the quantification of some of the cardiorespiratory responses to predominantly static exercises using small and different muscle groups and with different percentages of maximal voluntary strength, have contributed to a better understanding of the mechanisms associated with IHT and similar exercises 14,15,[33][34][35][36][37] . Nevertheless, when these physiological data, respecting the methodological differences and small samples involved, are compared with our results, one can identify a 13 .…”
Section: Discussionmentioning
confidence: 99%